Weycombe [large type] : a novel of suspense - Malliet, G. M., 1951- (Thorndike Press, a part of Gale, a Cengage Company, 2018)
Weycombe is the chocolate-box village of everyones dreams. For American Jillian White, a gated life of pleasure and comfort with her titled English husband was a fantasy come true. But the murder of a local estate agent mars the villages so-pretty surface. Are people actually dying to live in Weycombe? Jill investigates, piecing together clues along the snaking paths and winding lanes of her adopted village. She knows truth has many versions, depending on who is doing the telling.